(untitled) (Bangladesh Journal of Medical Science, 2017)
Ankyloglossia is a condition where there is a limitation to the tongue movement due to the congenitally short frenulum. This condition eventually lead to early weaning and poor weight gain. Frenotomy, or tongue tie division can be performed by few methods. Iris scissors or scalpel traditionally has been used. In adults a muscle release may be needed to give a good muscle tension upon closing. Laser use in adult has been described. We utilized ultrasonic scissors in this case. Bangladesh Journal of Medical Science Vol.16(2) 2017 p.332-333